The effect of the project-based learning model in Pancasila education on the creativity of primary school students - Kurniawati, Dita (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
Creativity is one of the essential competencies that should be developed from the early stages of education, including in Pancasila Education, which aims to cultivate students’ character, thinking abilities, and social skills. However, conventional teaching practices often limit students’ opportunities to explore ideas and express their creative potential. Therefore, an instructional model that encourages students’ active engagement in the learning process is required. This study aims to examine the effect of the Project-Based Learning (PjBL) model on students’ creativity in Pancasila Education. The research employed a quantitative approach using an experimental method with a one-group pretest–posttest design. The research subjects consisted of 22 students. The research instrument was a creativity test administered before and after the treatment. Data analysis was conducted using descriptive statistics, a normality test, and a Paired Samples T-Test with IBM SPSS 25. The results indicate that the mean score increased from 40.00 in the pretest to 70.05 in the posttest, with a significance value of 0.000 < 0.05. Thus, it can be concluded that the implementation of Project-Based Learning in Pancasila Education significantly influences the improvement of students’ creativity.